2018
DOI: 10.1002/dmrr.3083
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy and inflammation in diabetic bone marrow

Abstract: Summary Diabetes impairs the bone marrow (BM) architecture and function as well as the mobilization of immature cells into the bloodstream and number of potential regenerative cells. Circadian regulation of bone immature cell migration is regulated by β‐adrenergic receptors, which are expressed on haematopoietic stem cells, mesenchymal stem cells, and osteoblasts in the BM. Diabetes is associated with a substantially lower number of sympathetic nerve terminal endings in the BM; thus, diabetic neuropathy plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 92 publications
(211 reference statements)
0
4
0
Order By: Relevance
“…It con rmed that HSCs play an important role in wound healing again. Previous studies have found that the number of HSCs in the peripheral blood of diabetic patients and mice is reduced and the differentiation potential is impaired [25]. Diabetic patients and diabetic animals often have di culties in wound healing [26].…”
Section: Discussionmentioning
confidence: 99%
“…It con rmed that HSCs play an important role in wound healing again. Previous studies have found that the number of HSCs in the peripheral blood of diabetic patients and mice is reduced and the differentiation potential is impaired [25]. Diabetic patients and diabetic animals often have di culties in wound healing [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that topical application of SP accelerates the healing of cutaneous wounds by upregulating vascular endothelial growth factor (VEGF) and transforming growth factor-beta 1 (TGF-β1), endothelial nitric oxide synthase (eNOS), and hypoxia-inducible factor 1-alpha (HIF-1a), as well as by stimulating fibroblast prolifera- tion and collagen deposition [17,18]. Diabetes is associated with bone marrow microenvironmental deficiencies and damaged mobilization of bone marrow stem cells (BMCs) [19][20][21]. Studies have shown that SP promotes diabetic wound healing by restoring the cellular activity of BMCs and enhances endothelial progenitor cell (EPC) mobilization [22,23].…”
Section: Sp and Dfusmentioning
confidence: 99%
“…SP promotes neovascularization through the recovery of blood flow and formation of an elaborate vascular network in ischemic wounds and shows anti-inflammatory effects by suppressing inflammation-mediated spleen enlargement and reducing tumor necrosis factor-alpha in ischemic mice [16]. Studies have shown that topical application of SP accelerates the healing of cutaneous wounds by upregulating vascular endothelial growth factor (VEGF) and transforming growth factor-beta 1 (TGF-β1), endothelial nitric oxide synthase (eNOS), and hypoxia-inducible factor 1-alpha (HIF-1a), as well as by stimulating fibroblast proliferation and collagen deposition [17,18] bilization of bone marrow stem cells (BMCs) [19][20][21]. Studies have shown that SP promotes diabetic wound healing by restoring the cellular activity of BMCs and enhances endothelial progenitor cell (EPC) mobilization [22,23].…”
Section: Sp and Dfusmentioning
confidence: 99%
“…We concluded that, in patients with advanced diabetic complications, microangiopathy and sensory neuropathy could cooperate in jeopardizing HSPCs fate and function within the BM before they are liberated into the circulation. A recent review article has summarized the knowledge on neuropathy and inflammation in diabetic bone marrow …”
Section: Pathogenic Phenomena Upstream Of Mobilopathymentioning
confidence: 99%